TA'ĀRUF ONLINE PERSPECTIVES ON FIQHIYYAH METHODS: DAR’U AL-MAFĀSID AULĀ MIN JALB AL-MAŞĀLIH - Rahim, Asrianto; Misbahuddin; Mujiburrahman; Nurfaika, Sitti; Razak, Abd. Rahman; Ramoddin; Zainuddin (Universitas Islam Negeri Alauddin Makassar, 2023)
Ta'aruf is one of the realms of social interaction which is the door to building a relationship between human beings in general. This has been discussed in the Qur'an which is a book that contains instructions for humans, that humans are created with different shapes or characters. The goal is for people to get to know each other. In other terms known as the term ta'aruf earlier. However, in this discussion the word ta'aruf is interpreted more specifically as an effort to recognize the opposite sex to be a life partner. So, ta'aruf is part of the initial stages before building a lasting relationship, namely marriage. Related to this, the law or sharia whose function is to fill the space for all community behavior, also follow these developments so that they can always provide explanations about new things that arise. The aim is to be able to provide legal certainty regarding a new lifestyle that is developing in society. This study uses the library method, namely by collecting as much data as possible from previous research and then concluding it into new research, it is intended that this research will later become one of the sources for similar discussions.